2011
DOI: 10.4238/2011.october.31.9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental effects on age at first farrowing in sows in southeastern Brazil

Abstract: ABSTRACT. We evaluated genetic and environmental factors affecting age at first farrowing of sows in the Brazilian southeast. For this purpose, 466 observations regarding the age at first farrowing were made for Dalland-C40 © animals belonging to two herds. The effects of the environmental factors on this trait were assessed by means of a model that included, as random effects, the influence of the sow's father and mother and, as fixed effects, the influence the year of birth, the herd and the birth season, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Our estimates of heritability for AFF were not consistent across breeds and connectedness groups (varied from 0.11 to 0.45). These estimates were in the range of those obtained in previous studies, which ranged from low (0.16) (Serenius et al, ), moderate (0.23) (Akanno et al, ; Knauer, Cassady, Newcom, & See, ) to high (0.44) (Cavalcante‐Neto et al, ). And the standard errors of heritability estimates for AFF in each connectedness group of all breeds were large, implying that the estimates are not reliable.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our estimates of heritability for AFF were not consistent across breeds and connectedness groups (varied from 0.11 to 0.45). These estimates were in the range of those obtained in previous studies, which ranged from low (0.16) (Serenius et al, ), moderate (0.23) (Akanno et al, ; Knauer, Cassady, Newcom, & See, ) to high (0.44) (Cavalcante‐Neto et al, ). And the standard errors of heritability estimates for AFF in each connectedness group of all breeds were large, implying that the estimates are not reliable.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, this variability in calculation for AFF could be or partly due to the small sample sizes (e.g., litters in Group 2–3 of Duroc pigs were <4,000), reflected by the relatively large standard errors (0.12–1.91) and the difficulty of data collecting. AFF can be considered as a comprehensive trait that combines age at first mating and gestation length, the phenotype varied largely in each connectedness group (see Table ) due to environmental factors and measurement error (Cavalcante‐Neto et al, ; Knauer et al, ; Serenius et al, ), resulting in the large variation of estimation of genetic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Bísaro pigs, the h 2 of AFF was 0.35 [ 43 ]. With a higher h 2 of 0.44 in sows, Cavalcante-Neto et al [ 44 ] presented further arguments. The h 2 value of 0.23 found by Akanno et al [ 38 ], based on a meta-analysis study, also reported some disagreement.…”
Section: Discussionmentioning
confidence: 99%